1999
DOI: 10.1080/00365519950185120
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and renal extraction of circulating type I procollagen aminopropeptide in patients with normal liver function and in patients with alcoholic cirrhosis

Abstract: The circulating level and splanchnic and renal extraction of serum type I procollagen aminoterminal propeptide (PINP) was studied in 20 patients with normal liver function and in 15 patients with alcoholic liver cirrhosis. In patients with alcoholic cirrhosis, the concentration of PINP in the femoral artery blood was significantly higher than in the group of patients with normal liver function (median 145 microg/l, 95% CI 98-195 versus 57 microg/l, 95% CI 42-92, p<0.001). A significant decrease in the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In extremely obese patients with an average body mass index of 44 kg/m 2 , liver biopsy confirmed that the increased stages of fibrosis were independently associated with higher levels of P1NP (29). The P1NP has also been reported to be related to liver fibrosis in other chronic hepatic diseases (10,30,31). In primary biliary cirrhosis patients, P1NP levels were higher than in controls (30).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In extremely obese patients with an average body mass index of 44 kg/m 2 , liver biopsy confirmed that the increased stages of fibrosis were independently associated with higher levels of P1NP (29). The P1NP has also been reported to be related to liver fibrosis in other chronic hepatic diseases (10,30,31). In primary biliary cirrhosis patients, P1NP levels were higher than in controls (30).…”
Section: Discussionmentioning
confidence: 76%
“…In alcoholic cirrhosis patients, the mean serum P1NP concentration was significantly higher than in the control group and appeared to vary depending on the severity of the liver damage (i.e., the concentration of P1NP was significantly higher in Child-Pugh class C than in class A) (10). The concentration of P1NP in the femoral artery blood was also significantly higher in patients with alcoholic cirrhosis than in patients with normal liver function (31).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As PINP propeptides in part are cleared by liver endothelial cells, and these cells may be injured secondary to inflammation due to the BDL, a part of the observed increase could be due to failure of damaged endothelial cells to clear PINP [35]. As an example, patients presenting with alcoholic liver fibrosis with acute inflammation, N-terminal propeptide of type III collagen (PIIINP), a marker of type III collagen formation, is significantly increased, whereas in cirrhosis, PIIINP is only moderately increased [8].…”
Section: Discussionmentioning
confidence: 99%
“…Procollagen by-products such as N-terminal propeptide from types I and III collagen (PIMP and PIIINP) have been largely studied as markers of both inflammation and fibrosis and appear to correlate well with advanced fibrosis/cirrhosis (with 0.72 and 0.76 AUROCs, respectively). 60 62 YKL-40, a glycoprotein associated with extracellular matrix remodeling expressed in hepatic stellate cells, has been found to correlate well with liver fibrosis with promising diagnostic performance in cirrhosis (AUROC 0.80). 63 , 64 Finally, serum concentrations of metalloproteinases and their inhibitors (matrix metalloproteinases and tissue inhibitor of metalloproteinases [TIMPs]), involved in extracellular matrix degradation, have also been correlated with advanced fibrosis and cirrhosis, but with less reliable prediction capabilities in significant fibrosis.…”
Section: Introductionmentioning
confidence: 99%